An income analysis of beef cattle fattening system and its contribution to the total household income in Central Java Province - Prasetyo, E.; Ekowati, T.; Gayatri, S. (Diponegoro University, 2020)
Beef cattle fattening is raised by farmers in Central Java, but not yet profit oriented. The aims of this research were to analyze the farmer income of beef cattle fattening farm and its contribution to the total household income and to analyze the influence of production costs and farm size toward beef cattle farm income. Survey was used among 150 beef cattle farmers, while multi stage cluster quota sampling was used as sampling method. Income analysis, paired t test, and multiple linear regression were used for data analysis. Research result showed that the farmer’s income from beef cattle farm is IDR 6,736,824.21 per 6.32 month fattening period on an average farm scale was 2.31 heads (equal to IDR 1,065,953.20/month). While, average income of farm households from non-beef cattle farm was IDR 3,516,080.95/month. The contribution of beef cattle farm to household farmer’s income was 30.32%. Based on the paired t test, beef cattle farm income is significantly different and smaller than the income from non-beef cattle farm. Multiple linear regression analysis showed that variable cost and number of beef cattle had a significant effect on beef cattle farm income, while the fixed cost had no significant effect.